Respuesta :
Answer:
y(t) =[tex]-34+10 t + 17 e^{-t} Sin(2 t) + 30 e^{-t} Cos(2 t)[/tex]
Step-by-step explanation:
We use the Laplace transform in the function y''(t) +2y'(t)+ 5y(t) =50t-150
ℒ{ y''(t) +2y'(t)+ 5y(t)} =ℒ{50t-150}
ℒ{ y''(t)} +2ℒ{y'(t)}+ 5ℒ{y(t)} =ℒ{50t-ℒ{150}
s²·Y(s)-s·y(0)-y'(0)+2s·Y(s)-2·y(0)+5·Y(s)=[tex]\frac{50}{s^2}-\frac{150}{s}[/tex]
s²·Y(s)-s·(-4)-(14)+2s·Y(s)-2·(-4)+5·Y(s)=[tex]\frac{50}{s^2}-\frac{150}{s}[/tex]
Y(s)·(s²+2s+5)+4s-14+8=[tex]\frac{50}{s^2}-\frac{150}{s}[/tex]
Y(s)·(s²+2s+5)=[tex]\frac{50}{s^2}-\frac{150}{s}[/tex]-4s+6
Y(s)·(s²+2s+5)=[tex]\frac{50-150s-4s^3+6s^2}{s^2}[/tex]
Y(s)=[tex]\frac{50-150s-4s^3+6s^2}{s^2(s^2+2s+5)}[/tex]
The new function can also be expressed as partials fractions:
Y(s)=[tex]\frac{50-150s-4s^3+6s^2}{s^2(s^2+2s+5)}[/tex]=[tex]\frac{A}{s}+\frac{B}{s}+\frac{Cs+D}{s^2+2s+5}[/tex]
Hence,
[tex]50-150s-4s^3+6s^2=[tex(]\frac{A}{s}+\frac{B}{s^2}+\frac{Cs+D}{s^2+2s+5}[/tex])×[s^2(s^2+2s+5)]
50-150s+6s²-4s³=(A+C)s³+(2A+B+D)s²+(5A+2B)s+(5B)
A+C=-4 ⇒ C=-4+34=30
2A+B+D=6 ⇒ D=64
5A+2B=-150 ⇒ A=-34
5B=50 ⇒ B=10
The function Y(s) is:
Y(s)=[tex]\frac{-34}{s}+\frac{10}{s^2}+\frac{30s+64}{s^2+2s+5}[/tex]
30s+64 can be expressed as:
30s+64= 30(s+1)+34
s²+2s+5 can be expressed as:
s²+2s+5=(s²+2s+1)-1+5=(s+1)²+4
Then:
Y(s)=[tex]\frac{-34}{s}+\frac{10}{s^2}+\frac{30(s+1)}{(s+1)^2+2^2}+\frac{17*2}{(s+1)^2+2^2}[/tex]
We use the inverse Laplace transform and find the transformation in the table:
ℒ⁻¹{Y(s}=ℒ⁻¹{[tex]\frac{-34}{s}+\frac{10}{s^2}+\frac{30(s+1)}{(s+1)^2+2^2}+\frac{17*2}{(s+1)^2+2^2}[/tex]}
y(t)=[tex] - 34 + 10 t + 17 e^{-t} Sin(2 t) + 30 e^{-t} Cos(2 t)[/tex]